Global Financial Crisis (2007-2008) and Foreign Direct Investment (FDI) Inflows' Resilience to other Capital Flows in Sub-Sahara African (SSA) Countries - Ezebunwa, Onu King (Research Parks Publishers, 2025)
: This study examines the effect of global financial crisis (2007-2008) on foreign direct investment inflows' resilience to other capital flows to selected Sub-Sahara African (SSA) Countries. This study was motivated by the assertion that foreign direct investment (FDI) inflows to developing economies are resilient than other capital inflows in 2007-2008 global financial crisis that originated in developed world. Specifically, the study ascertained whether foreign direct investment (FDI) inflow is significantly resilient than foreign portfolio investment (FPI) inflow in SSA. Using panel datasets from 26 SSA countries, the study explored non-stationarity and heterogeneous – based dynamic panel estimators namely, Mean Group (MG) and Pooled Mean Group to empirically implement the objectives. The findings of the study amongst others revealed significant evidence of the resilience of the inflow of foreign direct investment to SSA during the global financial crisis period of (2007 – 2008), contrary to the wide-spread assertion that developing economies are immune to the impact of the crisis. Also, we found that the foreign direct investment (FDI) inflow is significantly resilient than foreign portfolio investment (FPI) inflows in SSA. This study recommends the policies that may stabilize growth of FDI inflows. Thus, more foreign investors should be attracted which should increase investment opportunities and growth in the region. Greater attention should be given to FDI whenever global financial crisis is experienced.